Supply-demand gap of provisions in the control of chronic kidney disease at EsSalud - Zanabria Calderón, José (2023)
Chronic Kidney Disease (CKD) is a public health problem. EsSalud has near of 10,800 patients on dialysis, investing about 12,000 dollars per patient per year, without considering the management of complications. The General Objective of the study is to estimate the supply-demand gap of preventive and recovery provisions in the control of CKD at EsSalud and the specific objectives are the following: to estimate the distribution of the stages of the CKD, to estimate the demand supply gap for preventive and recovery provisions and to estimate the institutional expense of EsSalud for the management of the CKD. The present investigation is an observational, descriptive, cross-sectional and correlational study of the patients whose diagnosis was, CKD, or arterial hypertension, diabetes and all persons over 55 years old. The main results were the following: the insured population by EsSalud at risk of CKD amounts to 4'839,065 people and its estimated 836,838 with the disease. The estimated prevalence of CKD on dialysis reached 0.099 %; the distribution of CKD has been estimated, applying the results of the NHANES III study of the USA by stages: 1: 3.3 %; 2: 3.0 %; 3: 4.34 %; 4: 0.2 % and 5: 0.1 %; the supply-demand gap for preventive provisions of the CKD for 2017 was negative; the supply-demand gap was positive for hemodialysis and negative for peritoneal dialysis and the institutional expenditure in the management of CKD reached 400.8 million soles representing 3.95 % of the budget. It is necessary to increase efforts for the disease prevention and of the disease.